Determination of heavy metals in selected estuary vegetation in the Muara Tebas estuary - Nur Afzan, Mohd Nasir (Universiti Malaysia Sarawak, UNIMAS, 2008)
Heavy metals are toxic substances that can cause harmful effects in organisms. Heavy metals are also one of the sources of toxicity in an environment. Most of the pollution at an estuary occurs because of the high concentrations of heavy metals at the estuary. Selected heavy metals i.e. iron (Fe), zinc (Zn), manganese (Mn) and cadmium (Cd) in selected estuary vegetation i.e. Sonneratia sp. and Avicennia sp. were studied. The concentrations of metals were determined by using the Atomic Absorption Spectrometry (AAS). Iron (Fe) was the most abundant metal found present in the estuary vegetation and in the sediments. Heavy metals investigated are a source of contamination for the estuary ecosystem.